Ingenious Artificial Leaf Based on Covalent Organic Framework Membranes for Boosting CO2 Photoreduction - Gao, Shuaiqi; Zhang, Qian; Su, Xiaofang; Wu, Xiangkun; Zhang, Xia-Guang; Guo, Yingying; Li, Zhiyong; Wei, Jishi; Wang, Huiyong; Zhang, Suojiang; Wang, Jianji (Journal of the American Chemical Society, 2023)
Covalent organic frameworks (COFs) hold the potential in converting CO2 with water into value-added fuels and O2 to save the deteriorating ecological environment. However, reaching high yield and selectivity is a grand challenge under metal-, photosensitizer-, or sacrificial reagent-free conditions. Here, inspired by microstructures of natural leaves, we designed triazine-based COF membranes with the integration of steady light-harvesting sites, efficient catalytic center, and fast charge/mass transfer configuration to fabricate a novel artificial leaf for the first time. Significantly, a record high CO yield of 1240 μmol g–1 in a 4 h reaction, approximately 100% selectivity, and a long lifespan (at least 16 cycles) were achieved under gas–solid conditions without using any metal, photosensitizer, or sacrificial reagent. Unlike the existing knowledge, the chemical structural unit of triazine-imide-triazine and the unique physical form of the COF membrane are predominant for such a remarkable photocatalysis. This work opens a new pathway to simulating photosynthesis in leaves and may motivate relevant research in the future.